The antidepressant effect of 4-hydroxybenzyl alcohol 2-naphthoate through monoaminergic, GABAergic system and BDNF signaling pathway. Issue 16 (17th August 2020) - Zhang, Di; Zhu, Hong-yan; Bian, Xing-bo; Zhao, Yan; Zang, Pu; Gao, Yu-gang; Zhang, Lian-xue
Abstract: Gastrodigenin, also known as 4-hydroxybenzyl alcohol (HBA), is one of the main components of Gastrodia elata, which is a perfect lead compound of natural products. In order to get new active compounds, we modified the structure of HBA through esterification with carboxylic acid, and got a series of derivatives in which 4-hydroxybenzyl alcohol 2-naphthoate (NHBA) showed stronger antidepressant activity than HBA. In this paper, we firstly evaluated the antidepressant activity of NHBA by tail suspension test (TST) and forced swimming test (FST). Then, we carried out the biochemical assay and western blot to determine its mechanism. The results displayed that NHBA could increase the content of serotonin, dopamine, norepinephrine, γ-aminobutyric acid, brain-derived neurotrophic factor (BDNF) and tropomyosin receptor kinase B (TrkB) in mice brain. It suggested that NHBA exhibited an antidepressant-like effect through monoaminergic system, GABAergic system and BDNF/TrkB signaling pathways. GRAPHICAL ABSTRACT: